The association of soluble Klotho levels with anemia and hemoglobin variability in hemodialysis patients. Issue 2 (9th August 2022) - Topal, Mustafa; Guney, Ibrahim
Abstract: Introduction: The anti‐aging protein Klotho levels are decreased, and Klotho deficiency is associated with cardiovascular diseases in patients with chronic kidney disease. There are recent studies about the relation between soluble Klotho levels and anemia. We aimed to investigate the correlation of anemia and hemoglobin variability with soluble Klotho levels in hemodialysis patients. Methods: Ninety‐one hemodialysis patients were included in this study. The mean hemoglobin value, hemoglobin variability, and coefficient of variation of hemoglobin for each patient were calculated. According to mean hemoglobin levels, two groups were defined as under 11 and ≥11 g/dl. Soluble Klotho levels of each patient were studied. Results: Mean hemoglobin levels, hemoglobin variability, and coefficient of variation of hemoglobin were not significantly correlated with soluble Klotho levels. According to mean hemoglobin levels under 11 and ≥ 11 g/dl, there was no statistically significant correlation between anemia and soluble Klotho levels. Conclusion: Soluble Klotho levels were not associated with anemia and hemoglobin variability in hemodialysis patients. Further studies are needed to reveal the complicated relation between anemia and soluble Klotho levels.